Desigualdad y pobreza en el Gran La Plata : Condiciones de vida en el Barrio José Luis Cabezas, Ensenada 2016 - Eguía, Amalia (Dir.) (Informes FaHCE, 2018)
This report presents the results of the census survey carried out in the José Luis Cabezas neighborhood during the months of October and November 2016.